2018
DOI: 10.1002/sia.6435
|View full text |Cite
|
Sign up to set email alerts
|

Surface changes of yttria‐stabilized zirconia in water and Hanks solution characterized using XPS

Abstract: Adhesion of soft and hard tissues to yttria-stabilized zirconia (YSZ) has been reported, despite its chemical inertness. To investigate the underlying mechanism of adhesion of hard and soft tissues to YSZ in dental implants, YSZ disks with (100), (110), and (111) crystalline planes were immersed in water for 60 days and in Hanks solution for 7 days, and the changes in the surface chemical states were characterized using X-ray photoelectron spectroscopy. After immersion in water for 60 days, the concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Hence, the reactivity of the Y-TZP surface may play an important role for tissue adhesion in human body. Such results were also demonstrated in single crystalline yttria-stabilized zirconia 10) . Based on the findings in Y-TZP reactivity to the water molecules and electrolytes in Hanks' solution, further studies are required for cell activities.…”
Section: Surface Reaction Of Y-tzpsupporting
confidence: 55%
See 1 more Smart Citation
“…Hence, the reactivity of the Y-TZP surface may play an important role for tissue adhesion in human body. Such results were also demonstrated in single crystalline yttria-stabilized zirconia 10) . Based on the findings in Y-TZP reactivity to the water molecules and electrolytes in Hanks' solution, further studies are required for cell activities.…”
Section: Surface Reaction Of Y-tzpsupporting
confidence: 55%
“…In addition, phosphate ions were incorporated into the surface and formed a phosphate, probably zirconium phosphate, on all YSZs without any reaction of calcium ions. Thus, the (110) plane was the preferential reaction site in YSZ 10) .…”
Section: Introductionmentioning
confidence: 96%
“…Figure 5 shows the XPS spectra of the electronic binding energies of Zr 3d, Mg 1s and O 1s for ZrO 2 , MgO and Mg/Zr-1.0. It can be observed that Zr and Mg in Mg/Zr-1.0 exist in the Zr 4+ oxidation state (181.78 and 183.98 eV) (Figure 5a) and Mg 2+ oxidation state (1304.18 eV) (Figure 5b), respectively [31]. The O 1s signal of Mg/Zr-1.0 is deconvoluted into three components: the Mg-O (530.0 eV), Mg-OH (530.7 eV), and H 2 O (533.4 eV) [32,33].…”
Section: Characterization Of the Synthesized Mgo/zro 2 Catalystsmentioning
confidence: 99%
“…[47] Peaks at 532 and 533.2 eV mean the presence of OH À and H 2 O, respectively, which further indicates that the product is hydroxide with water. [48] Meanwhile, the peak of 533.2 eV also indicates the possibility of the presence of C─O compound impurities. [49] The thermal decomposition process of green powders was characterized by the TG curve.…”
Section: Formation Mechanism Of Electrolytic Green Powdersmentioning
confidence: 99%